Using the Unified Theory of Acceptance and Use of Technology (UTAUT) and e-health literacy(e-HL) to investigate the tobacco control intentions and behaviors of non-smoking college students in China: a cross-sectional investigation - Yuanyuan Ma; Mengxia Zhou; Wenli Yu; Ziyue Zou; Pu Ge; Zheng Feei Ma; Yuting Tong; Wei Li; Qiyu Li; Yunshan Li; Siya Zhu; Xinying Sun; et al. (BMC, 2023)
Abstract Background Non-smoking college students are starting to smoke in increasing numbers, which shows that their tobacco control situation seems not optimistic. The UTAUT and e-HL are commonly used models and theories to predict health behaviors, while there are few studies on tobacco control. This paper aims to study the influencing factors of tobacco control intention and behavior of non-smoking college students in China by combining the UTAUT and e-HL. Methods Based on the stratified sampling method, 625 college students from 12 universities were selected. Data were collected using a self-made questionnaire designed based on the UTAUT and e-health literacy scales. Data were analyzed by SPSS 22 and AMOS 26, including descriptive statistics, one-way variance analysis and structural equation model analysis. Results The results of one-way variance analysis showed that there were significant differences in the score of non-smoking college students' tobacco control intention or behavior by hometowns, monthly living expenses, and parents' smoking history. Performance expectancy, effort expectancy, social influence had direct positive effects on behavioral intention. Facilitating condition, behavioral intention had direct positive impacts on use behavior and e-HL had an indirect positive impact on use behavior. Conclusions The combination of the UTAUT and e-HL can be used as an appropriate framework to predict the influencing factors of non-smoking college students' intention and behavior of tobacco control. Improving performance expectancy, effort expectancy, and e-HL among non-smoking college students, creating positive social environments, and providing facilitating condition are key aspects of increasing their tobacco control intention and behavior. It is also beneficial to promote the implementation of smoke-free campus and smoke-free family projects.